1966
DOI: 10.1128/aem.14.5.794-801.1966
|View full text |Cite
|
Sign up to set email alerts
|

Medium Without Rumen Fluid for Nonselective Enumeration and Isolation of Rumen Bacteria

Abstract: Beltsville, Md.), AND MARVIN P. BRYANT. Medium without rumen fluid for nonselective enumeration and isolation of rumen bacteria. Appl. Microbiol. 14:794-801. 1966.-Colony counts which approximated those in a habitat-simulating, rumen fluid-agar medium (RFM) were obtained in medium 10, a medium identical to the RFM except for the replacement of rumen fluid with 1.5 X 10-6 M hemin, 0.2% Trypticase, 0.05% yeast extract, and a 6.6 X 10-2 M volatile fatty acid mixture qualitatively and quantitatively similar to tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
207
2
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 397 publications
(213 citation statements)
references
References 13 publications
3
207
2
1
Order By: Relevance
“…Pounden & Hibbs (1948) concluded that with changes in ration there must be considerable adaptation of the 00ra to meet the changed nutritional conditions. Such variations have been reported (Gutierrez, Davis, Lindahl & Warwick, 1959;Bryant, Robinson & Lindahl, 1961;Caldwell & Bryant, 1966; Thorley, Sharpe & Bryant, 1968;Mann, 1970). However, only in a very few experiments have attempts been made to relate changes in rumen fermentation products to the microbial flora.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…Pounden & Hibbs (1948) concluded that with changes in ration there must be considerable adaptation of the 00ra to meet the changed nutritional conditions. Such variations have been reported (Gutierrez, Davis, Lindahl & Warwick, 1959;Bryant, Robinson & Lindahl, 1961;Caldwell & Bryant, 1966; Thorley, Sharpe & Bryant, 1968;Mann, 1970). However, only in a very few experiments have attempts been made to relate changes in rumen fermentation products to the microbial flora.…”
mentioning
confidence: 62%
“…The procedure for the preparation of media, isolation and identification were essentially the same as those given by Caldwell & Bryant (1966) modified by Latham & Sharpe (1971). All incubations were a t 39".…”
Section: Enuilaeration and Isolation Of Rumen Organismsmentioning
confidence: 99%
“…Two mature Standardbred castrate male horses with normal feet were dosed with 12.5 g kg À1 live weight oligofructose (Raftilose P95Ò) 1 by nasogastric intubation and developed laminitis prior to slaughter at 48 h. These two horses were part of a group of eight horses used in an experiment aimed at developing a horse, hind gut acidosis and laminitis induction model using oligofructose (OF). Blood samples were collected from the two horses dosed with OF and from two sham-infected horses at 0, 4,8,12,16,20,24,28,32,36,40,44, and 48 h after dosing for the analysis of D-lactate. Four mature Australian stock horses (2 castrate males and 2 females) were fed medium quality grass hay, two of which were deprived of feed and water for 6 h prior to slaughter while the other two had access to feed and water ad libitum.…”
Section: Animals and Experimental Dietsmentioning
confidence: 99%
“…Following the addition of 10 mL anaerobic 0.1% peptone water, the pellets were mixed to obtain homogenous slurries, and subjected to a 10-fold dilution series. Dilutions were plated on L-10 anaerobic medium to obtain the total anaerobic count (Caldwell & Bryant, 1966) and de Man-Rogosa-Sharpe medium (De Man, Rogosa, & Sharpe, 1960) for total lactobacilli. Plates were incubated in an atmosphere of H 2 /CO 2 /N 2 (10:20:70) at 38°C for 48 h, and the dilution plate having 30-300 colonies counted, with final counts expressed in terms of percentage of the total anaerobic count.…”
Section: Fecal Community Analysismentioning
confidence: 99%